Investigating Debates Around Racism in Sport to Facilitate Perspective Transformation in the Secondary English Classroom - Merga, Margaret; Booth, S. (2017)
The English classroom is a space in which issues of social justice can be explored through texts, using a critical literacy approach. Indigenous Australians have been subject to racist policies throughout postcolonial Australian history, and racist attitudes toward Australia’s original inhabitants prevail. This article suggests that racism in the Australian Football League online discourse community can be addressed in the English classroom, as social media texts in this area provide rich illustration of the prevailing antisocial attitudes thriving both in this community and the broader Australian community. Informed by both critical literacy and transformative learning theory (TLT), this article proposes a learning experience to facilitate perspective transformation in a secondary classroom. This experience draws on TLT to construct an experience incorporating introspection, stimulating awareness, reflection, and action. This experience is proposed in the hope that reticence to directly challenge antisocial views in the classroom may be overcome.